Labor force shortage in Russian regions - Ryazantsev, Sergey V.; Bragin, Alexey D.; Ochirova, Galina N. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Ėkonomika, 2021)
The article provides an overview of the current state of the labor market in the regions of the Russian Federation, analyzes the level and reasons for the shortage of labor resources, and the factors that have a direct impact on it. It was determined that the main problem is the shortage of labor resources caused by different reasons, such as unemployment, difficult demographic situation, and other complex factors since the federal subjects of Russia are highly differentiated by the level of socio-economic development, demographic, economic, social, geographic, climatic, and other characteristics. In the empirical part of our study, we identified relevant indicators that, in our opinion, fully highlight the changing situation in the regions as well as calculated the percentage dynamics of the level of registered unemployed and the need of organizations to fill vacancies. Subsequent empirical comparative analysis of selected indicators in three-year dynamics reveals that the need of organizations for workers to fill vacancies has an increasingly dynamic, while the unemployment rate is decreasing what shows a satisfactory dynamic. Based on the data obtained, it can be concluded that the shortage of labor resources is evident only in the Belgorod region, the Republic of Mordovia, and the Republic of Buryatia.